Endonucleolytic processing of covalent protein-linked DNA double-strand breaks - Neale, Matthew J.; Pan, Jing; Keeney, Scott (Nature (London), 2005)
DNA double-strand breaks (DSBs) with protein covalently attached to 5′ strand termini are formed by Spo11 to initiate meiotic recombination 1 , 2 . The Spo11 protein must be removed for the DSB to be repaired, but the mechanism for removal is unclear 3 . Here we show that meiotic DSBs in budding yeast are processed by endonucleolytic cleavage that releases Spo11 attached to an oligonucleotide with a free 3′-OH. Two discrete Spo11–oligonucleotide complexes were found in equal amounts, differing with respect to the length of the bound DNA. We propose that these forms arise from different spacings of strand cleavages flanking the DSB, with every DSB processed asymmetrically. Thus, the ends of a single DSB may be biochemically distinct at or before the initial processing step—much earlier than previously thought. SPO11–oligonucleotide complexes were identified in extracts of mouse testis, indicating that this mechanism is evolutionarily conserved. Oligonucleotide–topoisomerase II complexes were also present in extracts of vegetative yeast, although not subject to the same genetic control as for generating Spo11–oligonucleotide complexes. Our findings suggest a general mechanism for repair of protein-linked DSBs.